The Hepatitis C Genotype 1 Paradox: Cost per Treatment Is Increasing, but Cost per Cure Is Decreasing - Stephen D Shafran (Canadian Journal of Gastroenterology and Hepatology)
Significant attention has been focused on the perceived increase in the cost of antiviral treatment for hepatitis C genotype 1 infection since the approval of the first direct-acting antiviral agents in 2011. Using Canadian list prices, the present analysis points out a paradox: while the cost per antiviral regimen is increasing, the cost per cure is decreasing, especially with interferon-free therapy. In a publicly funded health care system, the lowest cost per cure is a more valuable measure of value for public money than the cost per regimen.